A Theoretical Overview of Alternative Economic Indicators GPI, SNBI and HDI - Csuvár, Ádám; Bánkuti, Gyögyi; Cseh, Balázs; Simon, Szabolcs; Varga, József (Acta Scientiarum Socialium, 2019)
The paper describes some of the main economic indicators such as the Genuine Progress Indicator (GPI), Sustainable Net Benefit Index (SNBI) and the Human Development Index (HDI) that have been intended to replace or supplement Gross Domestic Product. Based on our analysis, we conclude that none of the indicators is still able to replace GDP because of the difficulties in data collection and the lack of sufficient objectivity in the types of information used. Meanwhile, each indicator draws attention to important trends that are not visible from GDP so they can provide useful signals for building and evaluating policies. The study was created for the Economics Seminar of Kaposvár (KAKTUSZ) which is organized annually by the Kaposvár University. It is closely related to the paper by Varga et al. (2018) titled “Theoretical overview of MEW and ISEW alternative economic indicators” (in the present issue) and can be conceived as a continuation of that.